Body composition and perceived stress through a calendar year in NCAA I female volleyball players - Hyatt, H. W.; Kavazis, A. N. (International Journal of Exercise Science, 2019)
International Journal of Exercise Science 12(5): 433-443, 2019. The aim of the study was to track changes of perceived stress and body composition across an entire calendar year in National Collegiate Athletic Association (NCAA) division I female volleyball players. We hypothesized that perceived stress and body composition would vary between the competitive season and off-season, with the largest changes occurring during time points prior to the onset and after the end of the competitive season. Eight female volleyball players participated in a longitudinal study. Body mass, body mass index (BMI), percent body fat, fat mass, and fat free mass were obtained during the early, mid, late, and off season and during the pre, early, mid, and late competitive season. The perceived stress scale-10 was used to appraise stress levels. BMI and body mass were significantly higher in pre-season compared to early-offseason. Changes in BMI between these points were due to increase in fat mass. Fat mass and percent body fat were significantly higher in pre-season compared to late off-season, mid-season, and late season. Perceived stress was significantly higher at the mid-season compared to early offseason. A significant positive correlation existed between BMI and body fat (p<0.05, r=0.69), while a significant negative correlation existed between percent body fat and perceived stress (p<0.05, r=0.34). Tracking body composition and perceived stress in collegiate female volleyball players can provide informative feedback on the training status and well-being of female collegiate athletes. Interestingly, it appears stress in these athletes may be more dependent upon the school session rather than participation in competitive sports.